Inovasi Pembangunan Sosial Inklusif: Studi Kasus Kebijakan Pelayanan Kesehatan Brigade Siaga Bencana Pemerintah Kabupaten Bantaeng Tahun 2008-2018 - M Syaeful Anam (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Provinsi Sumatera Utara, 2025)
The implementation of developmentalism-orientated has resulted in social exclusion. A new development approach is needed to bring about social inclusion. This paper aims to examine the health service policy of the “Brigade Siaga Bencana” of Bantaeng Regency Government in 2008-2018. It seeks to analyse the policy innovation using a sociological perspective and Midgley's (2014) conception of social development. This research uses data obtained through literature study. The data are in the form of reports and research results from government and non-government institutions, scientific articles on social development and social policy, and news articles that discuss the Bantaeng District Government's “Brigade Siaga Bencana” policy. The findings of this study show that the Bantaeng District Government's “Brigade Siaga Bencana” health service policy is an inclusive social development effort. This policy provides increased and equitable access to health for vulnerable groups. Through the programme, maternal and infant mortality rates were reduced. The innovation took place within a decentralised structure, where local governments have the authority to develop the region according to local priorities, urgency and potential. Decentralisation requires participatory and collaborative governance to drive the social development agenda. The social development agenda through health services focuses on providing and protecting the basic rights of citizens. The implementation of the policy shows a transformation; from social exclusion to social inclusion in the health sector. This innovation can work through the collaboration of the state, private and civil society sectors. On the other hand, the policy has not encouraged empowerment, so the policy tends to be carried out in a populist manner. The policy depends on the populist leader's agenda, which aims to strengthen political position. The implication is that the policy is not sustainable. Keywords: innovation, inclusive social development, Brigade Siaga Bencana, Bantaeng